Physiotherapist-led treatment for femoroacetabular impingement syndrome (the PhysioFIRST study): a protocol for a participant and assessor-blinded randomised controlled trial. Issue 4 (7th April 2021) - Kemp, Joanne L; Johnston, Richard T R; Coburn, Sally L; Jones, Denise M; Schache, Anthony G; Mentiplay, Benjamin F; King, Matthew G; Scholes, Mark J; De Oliveira Silva, Danilo; Smith, Anne; McPhail, Steven M; Crossley, Kay M
Abstract : Introduction: This double-blind, randomised controlled trial (RCT) aims to estimate the effect of a physiotherapist-led intervention with targeted strengthening compared with a physiotherapist-led intervention with standardised stretching, on hip-related quality of life (QOL) or perceived improvement at 6 months in people with femoroacetabular impingement (FAI) syndrome. We hypothesise that at 6 months, targeted strengthening physiotherapist-led treatment will be associated with greater improvements in hip-related QOL or greater patient-perceived global improvement when compared with standardised stretching physiotherapist-led treatment. Methods and analysis: We will recruit 164 participants with FAI syndrome who will be randomised into one of the two intervention groups, both receiving one-on-one treatment with the physiotherapist over 6 months. The targeted strengthening physiotherapist-led treatment group will receive a personalised exercise therapy and education programme. The standardised stretching physiotherapist-led treatment group will receive standardised stretching and personalised education programme. Primary outcomes are change in hip-related QOL using International Hip Outcome Tool-33 and patient-perceived global improvement. Secondary outcomes include cost-effectiveness, muscle strength, range of motion, functional task performance, biomechanics, hip cartilage structure and physical activity levels. Statistical analyses will make comparisons between both treatment groups by intention to treat, with all randomised participants included in analyses, regardless of protocol adherence. Linear mixed models (with baseline value as a covariate and treatment condition as a fixed factor) will be used to evaluate the treatment effect and 95% CI at primary end-point (6 months). Ethics and dissemination: The study protocol was approved (La Trobe University Human Ethics Committee (HEC17-080)) and prospectively registered with the Australian New Zealand Clinical Trials Registry. The findings of this RCT will be disseminated through peer reviewed scientific journals and conferences. Patients were involved in study development and will receive a short summary following the completion of the RCT. Trial registration number: ACTRN12617001350314